2020
DOI: 10.1021/acs.energyfuels.0c02553
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cryogenic Liquid Nitrogen on the Morphological and Petrophysical Characteristics of Tight Gas Sandstone Rocks from Kirthar Fold Belt, Indus Basin, Pakistan

Abstract: Tight gas sandstone production faces enormous challenges from marginal matrix porosity and permeability in rock formations. In this regard, the liquid nitrogen (LN 2 ) treatment remedy has been suggested as an appropriate stimulation approach to resolve this issue. An experimental study was carried out to investigate the cryogenic liquid nitrogen fracturing of tight rock sandstone to enhance gas recovery from such reservoirs. Three core samples from the Kirthar fold belt were subjected to LN 2 treatment for 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 63 publications
1
34
0
Order By: Relevance
“…By performing physical experiments in the laboratory, Qin et al (2017) found that cyclic freezethaw by liquid nitrogen (CFT-LN 2 ) changed the permeability, porosity and pore structure of coal. Mahesar et al (2020a) and Cai et al (2015) believed that LN 2 could not only cause thermal cracks on the surface of coal rock samples, but also induce macro-fractures. After LN 2 treatment, the strength decreased by 16.18%-33.74%; the permeability was enhanced by more than 48%; the porosity rose by over 100%; and the nano-indentation modulus dropped linearly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By performing physical experiments in the laboratory, Qin et al (2017) found that cyclic freezethaw by liquid nitrogen (CFT-LN 2 ) changed the permeability, porosity and pore structure of coal. Mahesar et al (2020a) and Cai et al (2015) believed that LN 2 could not only cause thermal cracks on the surface of coal rock samples, but also induce macro-fractures. After LN 2 treatment, the strength decreased by 16.18%-33.74%; the permeability was enhanced by more than 48%; the porosity rose by over 100%; and the nano-indentation modulus dropped linearly.…”
Section: Introductionmentioning
confidence: 99%
“…(2017) found that cyclic freeze-thaw by liquid nitrogen (CFT-LN 2 ) changed the permeability, porosity and pore structure of coal. Mahesar et al. (2020a) and Cai et al.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, nanotechnology, in particular nanoparticles (NPs), has received increased attention in the oil and gas industry. This includes Chemical EOR (CEOR) application, which are widely used to produce more oil from unconventional oil reservoirs or once water flooding produce no more oil economically. NPs have recently been suggested as CEOR agents that can be used as dispersion in water or in combination with other chemicals such as brine, CO 2 , surfactants, polymers, or surfactant–polymer solutions. In real reservoir situations, the presence of organic acids is the main factor, which changes the wettability of typical reservoir formation to oil-wet, which may have a significant impact on CO 2 trapping capacities (note that CO 2 injection into typical formation may also have a substantial impact on wettability and asphaltene precipitation). , Recent studies have also shown that NPs can be used as a reversing agent for CO 2 -wet surfaces to hydrophilic surfaces for its implications on CO 2 -geological storage. The type and properties of chemicals formulated with NPs usually depend on the type and condition of the targeted oil reservoirs and the specific application. , For instance, polymer flooding, a classic chemical EOR (CEOR) technique, was originally suggested to be a practical alternative for water flooding in unconventional reservoirs that contain heavy (viscous) crude oils. , However, certain reservoir conditions, such as high salinity, increased temperature, or various heterogeneity, can dramatically reduce the feasibility of polymer flooding. Limitations such as chemical degradation and polymer solution instability can drastically affect the efficiency of the polymer as an EOR agent. , Synthetic fluids that use nanosized materials, internal breakers, and low molecular weight surface active materials can be used to achieve the performance of cross-linked polymer fluids and overcome the limitations of the polymer…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of SiO 2 and a water-soluble ethylene oxide-based nanocomposite with enhanced viscosity has been reported . Nonaqueous/nanofluid-polymer formulations can also be used as fracturing fluids to unlock tight gas or shale gas. Researchers have consistently studied the effect of different NPs on the rheological characteristics of nanofluids (NFs) for EOR purposes. The effect of various nanoparticles such as SiO 2 , Al 2 O 3 , and TiO 2 containing NFs on the viscosity behavior of oil has been investigated .…”
Section: Introductionmentioning
confidence: 99%